Perlindungan Hak Cipta atas Karya Fotografi dalam Promosi Destinasi Wisata Jakarta di Media Sosial - Dyah Arrum Ibna Suwita; Elisiyah Rahmah; Evi Fauziah Muda (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The development of digital technology has encouraged the widespread use of photography to promote tourist destinations on social media. However, the ease of access and dissemination of visual content often leads to copyright infringement on photographers. This study aims to analyze the legal protection of photographic works in the context of tourist destination promotion in Jakarta, as well as to identify challenges and solutions. The method used is a normative-juridical approach, analyzing relevant laws and regulations, such as Law Number 28 of 2014 concerning Copyright, as well as a case study of the use of tourist destination photos on social media by government agencies and tourism industry players. The results indicate that, normatively, photographic works are protected as creations with economic and moral value to their creators. However, the implementation of protection in the digital realm remains weak due to a lack of legal awareness, the difficulty of proving violations, and weak oversight of content on social media. Protection efforts can be strengthened through increased digital legal literacy, the implementation of open licenses (creative commons), and collaboration between the government, photographers, and tourist destination managers.